The Concept of Homeland in Uzbek Jadid Poetry (Third Sector Social Economic Review, 2025)
Although the late 19th and early 20th centuries in the geography of Turkistan mark a period of significant decline in social, political, economic, and cultural terms, this era also represents a time when, within the framework of modernization, intellectuals began questioning the existing conditions and seeking ways to escape the dire circumstances they were facing. It is also the period during which the spirit of national awakening emerged, alongside efforts toward reform and innovation. The intellectuals of the National Awakening Period became, in essence, the spokespersons of Turkistan through the struggles they undertook for their homeland. In their poetry, shaped by the political, social, and cultural conditions of their time, they addressed themes related to the homeland. At times, they directly used the terms Turkistan and Turkestani to denote their subject and audience; in situations where they could not employ these terms directly, they opted to express them indirectly through words such as Islam, Muslim, and the East. In either case, they sought to articulate their thoughts and emotions regarding the condition of Turkistan, its devastated state, and the struggle for a free Turkistan. The poets of this period conveyed in their poetry that the people of Turkistan had abandoned the civilization their ancestors had established, the scientific legacy they had created, the works they had written, and the truly patriotic intellectuals they had once produced – instead choosing ignorance, which, in turn, led to the destruction of their homeland by invaders. The intellectuals of the National Awakening Period endeavored to open the eyes of the Turkestani people by comparing the lifestyles, as well as the social and economic conditions, of Western and Eastern societies, thereby enabling them to take heed from the truths revealed through such comparisons.
Keywords: Turkestan; Jadid; homeland; literature; poetry